A review and analysis of the clinical literature on Charcot–Marie–Tooth disease caused by mutations in neurofilament protein L. Issue 3 (3rd June 2021) - Stone, Elizabeth J.; Kolb, Stephen J.; Brown, Anthony
Abstract: Charcot–Marie–Tooth disease (CMT) is one of the most common inherited neurological disorders and can be caused by mutations in over 100 different genes. One of the causative genes is NEFL on chromosome 8 which encodes neurofilament light protein (NEFL), one of five proteins that co‐assemble to form neurofilaments. At least 34 different CMT‐causing mutations in NEFL have been reported which span the head, rod, and tail domains of the protein. The majority of these mutations are inherited dominantly, but some are inherited recessively. The resulting disease is classified variably in clinical reports based on electrodiagnostic studies as either axonal (type 2; CMT2E), demyelinating (type 1; CMT1F), or a form intermediate between the two (dominant intermediate; DI‐CMTG). In this article, we first present a brief introduction to CMT and neurofilaments. We then collate and analyze the data from the clinical literature on the disease classification, age of onset and electrodiagnostic test results for the various mutations. We find that mutations in the head, rod, and tail domains can all cause disease with early onset and profound neurological impairment, with a trend toward greater severity for head domain mutations. We also find that the disease classification does not correlate with specific mutation or domain. In fact, different individuals with the same mutation can be classified as having axonal, demyelinating, or dominant intermediate forms of the disease. This suggests that the classification of the disease as CMT2E, CMT1F or DI‐CMTG has more to do with variable disease presentation than to differences in the underlying disease mechanism, which is most likely primarily axonal in all cases.